Hubungan Kualitas Pelayanan Persalinan Dengan Kepuasan Ibu Bersalin di Rumah Sakit Ibu dan Anak (RSIA) Sriratu Medan Tahun 2019 - Putri Ndruru, Desi Lustiyani; Wau, Herbert; Manalu, Putranto (Preventia: The Indonesian Journal of Public Health, 2019)
Health development to increase awareness, willingness, and the ability of everyone to be able to behave in a healthy life to achieve the specified health status. Quality health services are efficient health services, in contrast health services that are lacking or not quality will make the organization's services very wasteful and exfoliate expensive costs. Based on the results of an initial survey that has been carried out, dataon maternal and maternal visits at the Sri Ratu Medan Mother and Child Hospital (RSIA) in the last 3 years showed a declining number in 2015 of 681 births, 2016 in 573 births, in 2017 a total of 2017 505 maternity mothers. This is because there has been alot of competition between hospitals regarding the quality of childbirth services which is sufficient to provide satisfaction for maternity mothers. Research objective was to know the relationship between service quality and maternal satisfaction at Sri Ratu's Mother and Child Hospital in Medan in 2019. The research method used is quantitative research with cross sectional research. The population in this study were maternity patients at RSIA Sri Ratu Medan with a total sample of 83 people. Analysis using chi square test with α <0.05.Research results shows the p-value between Physical Evidence (p-value 0.001), Reliability (p-value 0,000), Responsiveness (p-value 0.001), Guarantee (p-value 0.115), Attention (p-value 0.243) on maternal satisfaction at RSIA Sri Ratu Medan in 2019. There is a supportive relationship between physical evidence, compatibility, responsiveness to maternal satisfaction and there is no relationship between assurance and attention to maternal satisfaction at Sri Ratu Hospital in 2019.